2022
DOI: 10.1200/jco.2022.40.17_suppl.lba3513
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of capecitabine plus concomitant radiation therapy followed by durvalumab (MEDI4736) as preoperative treatment in rectal cancer: PANDORA study final results.

Abstract: LBA3513 Background: The combination of capecitabine plus long course radiotherapy (RT) is the standard preoperative therapy in cT3-4 cN+ rectal cancer. pathologic complete remission (pCR) can be considered as surrogate endpoint of efficacy of treatment in terms of disease-free survival (DFS). Preclinical data points heavily toward a strong synergy between RT and immune treatments. Methods: This is a prospective phase II, open label, single arm, multicentre study in patient with locally advanced rectal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…All 13 protocols of the clinical studies considered radiotherapy always in conjunction with chemotherapy; 7 of 13 trials scheduled the immunotherapy after the induction of radiotherapy, [ 27 33 ] with four study protocols prescribing it concurrently, [ 34 37 ] one scheduling it before, [ 38 ] and one administering it either before or after SCRT. [ 39 ] Seven trials implemented PD-1 inhibitor therapy [ 27 , 28 , 35 39 ] and six used a PD-L1 agent, [ 29 34 ] with most (8/13) reporting results on MSS LARC. [ 27 , 28 , 32 34 , 36 , 37 , 39 ] In those, the pCR ranged from 22.2% to 66.6%, with most of the trials (5/8) using a PD-1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All 13 protocols of the clinical studies considered radiotherapy always in conjunction with chemotherapy; 7 of 13 trials scheduled the immunotherapy after the induction of radiotherapy, [ 27 33 ] with four study protocols prescribing it concurrently, [ 34 37 ] one scheduling it before, [ 38 ] and one administering it either before or after SCRT. [ 39 ] Seven trials implemented PD-1 inhibitor therapy [ 27 , 28 , 35 39 ] and six used a PD-L1 agent, [ 29 34 ] with most (8/13) reporting results on MSS LARC. [ 27 , 28 , 32 34 , 36 , 37 , 39 ] In those, the pCR ranged from 22.2% to 66.6%, with most of the trials (5/8) using a PD-1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pCR was reported in the PANDORA trial (32.7%), albeit with capecitabine and LCRT. [ 29 ] In the PANDORA and R-IMMUNE trials, the comparison is less challenging; both studies have a similar number of patients (19 and 26, respectively) and prescribe PD-L1 inhibitors (durvalumab and atezolizumab, respectively); however, PANDORA reported higher pCR rates than R-IMMUNE (32.7% and 24%, respectively). [ 29 , 30 ] Neither of those trials reported on the microsatellite status of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations